Designing a Digital Medical Management Training Simulator Using Distributed Cognition Theory. (February 2017) - Rybing, Jonas; Prytz, Erik; Hornwall, Johan; Nilsson, Heléne; Jonson, Carl-Oscar; Bang, Magnus
Background . Training of medical professionals is important to improve care during mass-causality events. Therefore, it is essential to extend knowledge on how to design valid and usable simulation-based training environments. Purpose . This article investigates how distributed cognition and simulation theory concepts can guide design of simulation-based training environments. We present the design and user evaluation ofDigEmergo, a simulator for training and assessing emergency medicine management. Design approach . A prior Distributed Cognition in Teamwork (DiCoT) analysis of the Emergo Train System (ETS) guided the design process. The design objective ofDigEmergo was to be useful, usable, retain distributed cognition features of ETS, and strengthen validity and output reliability. Evaluation . Eight expert ETS instructors participated in a formative system evaluation. The Technology Assessment Model (TAM) questionnaire was used to measure usefulness and ease of use. Observations and post-test interviews were conducted to contextualize the measures. Results . The results showed thatDigEmergo was perceived as somewhat to quite useful and somewhat easy to use. Overall, expert users consideredDigEmergo promising and successful in retaining core ETS features. Conclusions . The study indicates that a design methodology based on distributed cognition and simulation theory can be successfully combined to guide simulator (re)design and strengthen simulator validity.